Effect of Exercise Training on Lipoprotein Subclass Particle Concentrations and Sizes in Older Women: Results from a Randomized Controlled Trial - Ryan R. Porter; Joshua R. Sparks; J. Larry Durstine; Sabra S. Custer; Raymond W. Thompson; Xuewen Wang (Geriatrics, 2023)
Background: Evidence suggests that lipoprotein subclass particles are critical markers of cardiovascular disease (CVD) risk. Older women have increased CVD risk related to age. The purpose of this study was to determine whether low and moderate doses of exercise influence lipoprotein subclasses. Methods: Women (60–75 years) were randomized into groups for 16 weeks of moderate-intensity exercise training at a low or moderate dose (33.6 and 58.8 kJ/kg body weight weekly, respectively). Lipoprotein subclasses were determined by nuclear magnetic resonance spectroscopy before and after the training. RESULTS: The average weekly exercise duration was 109 and 164 min, for low- and moderate-dose groups, respectively. In the low-dose group, high-density lipoprotein particle (HDL-P) concentration decreased (Δ = −1.9 ± 3.1 µmol/L, mean ± SD, p = 0.002) and mean HDL-P size increased (Δ = 0.1 ± 0.3 nm, p = 0.028). In the moderate-dose group, mean HDL-P size (Δ = 0.1 ± 0.2 nm; p = 0.024) and low-density lipoprotein particle size increased (Δ = 0.4 ± 3.9 nm; p = 0.007). Baseline body mass index, peak oxygen consumption and age were associated with changes in a few lipoprotein subclasses. Conclusions: In this sample of inactive older women, moderate-intensity exercise training at a dose equivalent to or even lower than the minimally recommended level by public health agencies induced changes in lipoprotein subclasses in line with reduced CVD risk. However, higher doses are encouraged for greater health benefits.